Increased risk of tuberculosis in patients with rheumatoid arthritis in Japan. Issue 12 (12th July 2006) - Yamada, T; Nakajima, A; Inoue, E; Tanaka, E; Hara, M; Tomatsu, T; Kamatani, N; Yamanaka, H
Abstract : Objective: To determine the risk for tuberculosis infection in patients with rheumatoid arthritis before the anti-cytokine era in Japan. Patients and methods: A database of a single-institute-based large observational cohort study for rheumatoid arthritis at the Institute of Rheumatology, Tokyo Women's Medical University, Tokyo, Japan, was analysed. Information on the history of tuberculosis infection was collected by patient self-reporting during April and October 2003. The age-adjusted incidence rate and relative risk for tuberculosis infection were investigated. Results: Among 5044 patients with rheumatoid arthritis, 483 (9.6%) patients claimed to have a history of tuberculosis infection before October 2002. The frequency of history of tuberculosis increased according to the age of the patient. Four cases of new-onset tuberculosis were identified among 5544 patients with rheumatoid arthritis during 1 year. The age-adjusted incidence of tuberculosis was 42.4/100 000 patients. The relative risk for tuberculosis was 3.21 (95% confidence interval (CI) 1.21 to 8.55), and that of men and women was 10.59 (95% CI 3.42 to 32.78) and 1.41 (95% CI 0.2 to 10), respectively. Conclusion: There was an increased risk of tuberculosis infection in Japanese patients with rheumatoid arthritis, especially in male patients before the introduction of anti-tumour necrosis factor treatment. These data should form the basis for the risk management of anti-cytokine treatment in Japan.